International Food Policy Research Institute (IFPRI) research data management and open access policy - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
In pursuit of its mandate to provide research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition in developing countries, the International Food Policy Research Institute (IFPRI) produces a wide range of publications, datasets, and other research-based information resources. IFPRI considers the outputs of its research to be international public goods and is committed to facilitating their widespread distribution and use by providing unrestricted public access. The Policy supersedes all previous IFPRI policies related to research dataset management, including those approved in 2000 and updated in 2010 and 2019 as well as the IFPRI Open Access Policy issued in 2012 and updated in 2019, specifically in relation to research data. It is also aligned with the IFPRI Policy on Intellectual Property, as approved by IFPRI’s Senior Management Team on November11, 2020.